Protective effect of faecal occult blood test screening for colorectal cancer: worse prognosis for screening refusers. Issue 1 (1st January 2002) - Niv, Y; Lev-El, M; Fraser, G; Abuksis, G; Tamir, A
Abstract : Background and aims: Screening for colorectal cancer (CRC) by faecal occult blood testing (FOBT) decreases CRC mortality by 15–33%. Compliance remains an obstacle to maximising the benefit of FOBT screening. We tested the hypothesis that individuals offered FOBT screening but refused would have an increased incidence and worse prognosis for CRC compared with those tested and with controls. Methods: Annual screening was offered to 3548 average risk individuals, ≥40 years of age, from a highly stable population. A total of 2538 agreed to testing (group 1) and 1010 (28%) refused (group 2). Another 1376 individuals were never offered the test and served as controls (group 3). The groups were followed for 11 years: a three year screening period (1985–1987) and an eight year follow up period at the end of the screening programme (1988–1995). Incidence, stage, and mortality were compared. Characterisation of refusers was completed in 188 and 130 subjects of groups 1 and 2, respectively. Results: In the screening phase, mortality from CRC was significantly lower in group 1 than in groups 2 and 3. The cumulative incidence of CRC in the eight year follow up period was 21 (0.88%), 23 (2.28%), and 13 (0.94%) in groups 1, 2, and 3, respectively. This shows a reduction of 61.4% in group 1 compared with group 2 (relative risk 0.28 (95% confidence interval (CI) 0.19–0.32)) (p<0.001) and 6.4% compared with group 3 (relative risk 0.93 (95% CI 0.93–1.00)) (NS). During follow up, group 1 subjects also demonstrated a decrease in advanced Dukes' stage and mortality rate by 80% and 64%, and 79% and 62%, compared with groups 2 and 3, respectively. Refusers were more likely to be male, of Asian-African descent, and more likely to smoke, consume more coffee, and less tea or dairy foods. Conclusions: When accepted, FOBT may protect against CRC for prolonged periods. Individuals who refuse FOBT have a significantly higher CRC incidence and mortality rates than those who accept testing.